Uniaxially aligned ceramic nanofibers obtained by chemical mechanical processing - Tararam, R. [UNESP]; Foschini, C. R. [UNESP]; Destro, F. B.; Simoes, A. Z. [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP] (Elsevier B.V., 2014)
For this study, we investigated a simple method to generate well aligned nanofibers over large areas using an organic polymer stretched over the substrate surface With this method, ZnO and CuO 3D parallel nanowire arrays were successfully prepared by calcinations of the polymer fibers. X-ray diffraction (XRD) analysis revealed that the copper oxide has a monoclinic structure while the zinc oxide has a hexagonal structure. Scanning electron microscopy (SEM) analysis showed ceramic nanofibers with an average diameter of 120 nm which were composed of small nanoparticles which are 10 nm in diameter. The ability to obtain uniaxially aligned nanofibers reveals a range of interesting properties with potential applications for sensors, catalysts and energy technologies. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ZnO; CuO; Nanofiber; Inorganic/polymer composites